Root Handling Affects Carboxylates Exudation and Phosphate Uptake of White Lupin Roots - Tiziani, Raphael; Mimmo, Tanja; Valentinuzzi, Fabio; Pii, Youry; Celletti, Silvia; Cesco, Stefano (Frontiers in Plant Science, 2020)
The reliable quantification of root exudation and nutrient uptake is a very challenging task, especially when considering single root segments. Most methods used necessitate root handling e.g. root dissecting/cutting. However, there is a knowledge gap on how much these techniques affect root physiology. Thus, this study aimed at assessing the effect of different root handling techniques on the phosphate (Pi) uptake and carboxylate exudation of white lupin roots. White lupin plants were grown hydroponically in a full and Pi-deficient nutrient solution for 60 days. Phosphate uptake and carboxylate exudation of cluster and non-cluster roots were measured using custom made cells 1, 4 and 8 hours after the onset of light. Three different experimental set-ups were used: i) without cutting the root apparatus from the shoots, nor dissecting the root into smaller root sections - named intact plant (IP); ii) separating the roots from the shoots, without dissecting the root into smaller sections– named intact root (IR); iii) separating the roots form the shoots and dissecting the roots in different sections – named dissected roots (DR). The sampling at 8 hours led to the most significant alterations of the root Pi uptake induced by the sampling method. Generally, roots were mainly affected by the DR sampling method, indicating that results of studies in which roots are cut/dissected should be interpreted carefully. Additionally, the study revealed that the root tip showed a very high Pi uptake rate, suggesting that the tip could act as a Pi sensor. Citrate, malate and lactate could be detected in juvenile, mature and senescent cluster root exudation. We observed a significant effect of the handling method on carboxylate exudation only at sampling hour 1 and 8, although no clear and distinctive trend could be observed. Results here presented reveal that the root handling as well as the sampling time point can greatly influence root physiology and therefore should not be neglected when interpreting rhizosphere dynamics.